2014
DOI: 10.1097/iae.0b013e3182979e33
|View full text |Cite
|
Sign up to set email alerts
|

Intravitreal Ranibizumab for Choroidal Neovascularization With Large Submacular Hemorrhage in Age-Related Macular Degeneration

Abstract: Intravitreal ranibizumab can be considered a beneficial approach for the management of choroidal neovascularization with flat large submacular hemorrhage secondary to age-related macular degeneration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 25 publications
1
20
0
1
Order By: Relevance
“…Our patients had a larger mean SMH area at baseline compared to those in previous studies; however, our results are comparable with those of previous studies with respect to SMH prognostic factors. 1,13,17 In cases with expected poor prognosis at baseline, other treatment options (pneumatic displacement or rTPA administration) should also be considered over or in combination with anti-VEGF therapy. However, there are few studies evaluating the efficacy of pneumatic displacement and/or rTPA, particularly for large SMH.…”
Section: Discussionmentioning
confidence: 99%
“…Our patients had a larger mean SMH area at baseline compared to those in previous studies; however, our results are comparable with those of previous studies with respect to SMH prognostic factors. 1,13,17 In cases with expected poor prognosis at baseline, other treatment options (pneumatic displacement or rTPA administration) should also be considered over or in combination with anti-VEGF therapy. However, there are few studies evaluating the efficacy of pneumatic displacement and/or rTPA, particularly for large SMH.…”
Section: Discussionmentioning
confidence: 99%
“…However, limited published data are available regarding its efficacy in predominantly hemorrhagic lesions due to CNV [23,29,30]. In a prospective interventional case series on 22 eyes with predominantly hemorrhagic CNV, Iacono et al demonstrated a significant improvement in BCVA (p = 0.04), even if only 6 patients presented with foveal involvement at baseline [23]. …”
Section: Discussionmentioning
confidence: 99%
“…Treatment was given according to standard practice with an initial loading phase of 3 monthly injections of 0.5 mg/0.05 ml ranibizumab, followed by a maintenance phase with further assessment every month, with repeated injections as judged necessary by the treating ophthalmologist on the basis of the detection of subretinal fluid or intraretinal fluid on OCT, leakage on FA, a BCVA reduction of ≥5 ETDRS letters and the appearance of any new hemorrhages on fundus examination [23]. …”
Section: Methodsmentioning
confidence: 99%
“…These two eyes were treated with either pneumatic displacement or intravitreal anti-VEGF monotherapy, both of which have been shown to be effective in treating submacular hemorrhage secondary to exudative AMD [19][20][21][22][23][24]. However, visual acuity failed to return to baseline values in both patients.…”
Section: Discussionmentioning
confidence: 99%